Singing it anew: David Malouf's Ransom (Journal of the Association for the Study of Australian Literature, 2011)
In 2009 David Malouf's Ransom was published to great critical and popular acclaim. Ransom presents itself very simply as a beautiful story about (among other things) loss, love, vulnerability and storytelling. But what does it mean to talk about the beautiful in writing? Etienne Gilson argues that writing is a making before it is a knowing or willing, so its primary concern is not a truth to be known or a good to be willed. Its primary concern is beauty. This paper explores how the beautiful operates in, and structures, Ransom.